Stern Flap for resistance reduction of planing hull craft: a case study with a fast crew boat model - Yaakob, Omar (Penerbit UTM Press, 2004)

(untitled)
The Study On Various Methods Of Reducing The Resistance Of Patrol Craft Have Been Carried Out By Many Researchers. These Methods Included The Application Of Stern Flaps, Stern Wedges, And Microbubble Injection. However, Due To Its Simplicity And Practicality, Stern Flap Is The Most Promising And Cost Effective Method. The Effect Of A Stern Flap On The Resistance Performance Of The Planing Hull Crew Boat Is Presented. Model Tests Were Conducted To Prove The Effectiveness Of The Stern Flap On Reducing Planing Hull Craft Resistance. Five Different Stern Flap Designs Were Tested As Part Of Systematic Investigation To Determine The Optimum Geometrical Characteristics Of The Stern Flap. Results Of Model Resistance Experiments Showed That Four Of The Flaps Tested Showed An Increase In Resistance While The Flap At Zero Degree Angle Reduced The Total Resistance By 7.2 Percent At 23 Knots, And An Average Reduction Rate Of 4.5 Percent. At 23 Knots, An 8.2 Percent Reduction In Effective Power Was Predicted.